Waves, tides, and shallow-water processes (Open University oceanography series., 1997)
The text begins by describing waves, their measurement and characteristics, their behaviour in shallow water, and unusual waves. Next, mainly theoretical aspects are considered of sediment movement and deposition by currents, before discussing wave action in the littoral zone, tidal current action on tidal flat and in estuaries, and the interaction of waves, tides, and river flow in deltas. Finally, we examine shelf-sea processes, including an outline of their mineral resources.